Budaya Organisasi Positif dan Kepengikutan Otentik Pelaku UMKM Wisata Pesisir Selatan Bangkalan - Triyo Utomo; Masrifah Masrifah; Seger Handoyo; Fajrianthi Fajrianthi (Universitas Trunojoyo Madura, 2023)
Bangkalan is an area that continues to grow. This development can occur because one of them is supported by the tourism sector on the coast. Based on this, the development of coastal tourism destinations needs support from various parties, one of which is MSME (Micro, Small and Medium Enterprises) actors. This study discusses the existing followership of MSME actors in Bangkalan's south coast tourism. One of the types of followership that has been widely discussed in the last few decades is authentic followership. One of the factors that influence authentic followership is a positive organizational culture. Based on this, this study aims to determine the effect of positive organizational culture on authentic followership. The method used in this research is a quantitative study of influence. Data collection was carried out using a scale on a sample of 130 MSME actors in the southern coastal tourism area of Bangkalan Regency. The sampling technique used is random sampling. The analysis technique uses simple linear regression and the data is processed with SPSS version 14 software. The results show that positive organizational culture influences authentic followership. Positive organizational culture has an influence of 32.6% on the authentic followership of MSME actors in the south coast of Bangkalan, while the remaining 67.4% is a variable that is not discussed in this study.